A comparative study of different battery geometries used in electric vehicles - Hummes, Diego Nieto; Hunt, Julian; Hervé, Bruno Barcellos; Schneider, Paulo Smith; Montanari, Pedro Marin (Latin American Journal of Energy Research, 2023)
This paper contributes with a review of current and future electric vehicle battery geometries, as there are few comparisons regarding performance criteria in the literature. With these considerations, this paper seeks to fill this gap by comparing commercial batteries with different geometries. First, the specifications of each battery (found on manufacturers’ websites or in specialized media) are presented. Then, the battery evaluation criteria are defined considering two distinct applications: economy and performance cars, using the Multi-Attribute Utility Theory (MAUT) method. From that analysis, the blade battery presented the best overall performance with a good rating for both applications. The cylindrical geometry followed with a rating suited better for performance vehicles, and the pouch geometry followed showing promise for use in economy-driven vehicles mostly. Lastly, a case study is carried out by evaluating the application of each of the batteries in a commercial vehicle. It was found that when compared to new technologies, the potential for improvement on any of the studied criteria is enormous. In particular, the Licerion pouch battery (Sion) showed the best performance regarding range and capacity-to-weight ratio, while the 4680 cylindrical battery (Panasonic) and blade battery (BYD) were superior in capacity-to-volume and capacity-to-cost ratios, respectively.